Some Notes on the French Delegation's Remarks Concerning the Interim Report - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Paul Messinesi Confidential memorandum from Mr. Messinesi to Mr. Jordan, Secretary of the Special Committee. The document contains the remarks of the French delegation to the UN General Assembly in French.